Motor skill learning and offline-changes in TGA patients with acute hippocampal CA1 lesions. (April 2017) - Döhring, Juliane; Stoldt, Anne; Witt, Karsten; Schönfeld, Robby; Deuschl, Günther; Born, Jan; Bartsch, Thorsten
Abstract: Learning and the formation of memory are reflected in various memory systems in the human brain such as the hippocampus based declarative memory system and the striatum-cortex based system involved in motor sequence learning. It is a matter of debate how both memory systems interact in humans during learning and consolidation and how this interaction is influenced by sleep. We studied the effect of an acute dysfunction of hippocampal CA1 neurons on the acquisition (on-line condition) and off-line changes of a motor skill in patients with a transient global amnesia (TGA). Sixteen patients (68 ± 4.4 yrs) were studied in the acute phase and during follow-up using a declarative and procedural test, and were compared to controls. Acute TGA patients displayed profound deficits in all declarative memory functions. During the acute amnestic phase, patients were able to acquire the motor skill task reflected by increasing finger tapping speed across the on-line condition, albeit to a lesser degree than during follow-up or compared to controls. Retrieval two days later indicated a greater off-line gain in motor speed in patients than controls. Moreover, this gain in motor skill performance was negatively correlated to the declarative learning deficit. Our results suggest a differential interaction between procedural and declarative memory systems during acquisition and consolidation of motor sequences in older humans. During acquisition, hippocampal dysfunction attenuates fast learning and thus unmasks the slow and rigid learning curve of striatum-based procedural learning. The stronger gains in the post-consolidation condition in motor skill in CA1 lesioned patients indicate a facilitated consolidation process probably occurring during sleep, and suggest a competitive interaction between the memory systems. These findings might be a reflection of network reorganization and plasticity in older humans and in the presence of CA1 hippocampal pathology.